دور العلاقات العامة في تحسين الاداء الوظيفي في المؤسسة الاقتصادية - سويد احمد, قمر; حمادي, سالمية (كلية العلوم الاجتماعية, 2019)
ملخص الدراسة: تمثلت مشكلة الدراسة في دور العلاقات العامة في تحسين اداء الموظفين في مؤسسة سونلغاز بتيندوف والأسباب التي دفعت بنا لاختيار هذا الموضوع ومحاولتنا اثراء موضوع العلاقات العامة وما تقدمه في الجانب الاقتصادي و بالتحديد في مؤسسة سونلغاز لكونها خدماتية بالدرجة الاولى ذات طابع اقتصادي و كذا اهمال دور العلاقات العامة في معظم المؤسسات . واعتمدنا في دراستنا لبلوغ الاهداف المرجوة على مجموعة من التساؤلات تتمثل: فيما تكمن نشاطات العلاقات وما هي مكانتها في الشركة؟ كيف تساهم العلاقات العامة في تحسين أداء الموظف في شركة سونلغاز؟ ما هي الصعوبات التي تواجه الموظف داخل الشركة؟ كما اعتمدنا على مجموعة من الفرضيات: ترتكز مصلحة العلاقات العامة على نشاطات تضمن تحسين الاداء الوظيفي لشركة سونلغاز تيندوف. تقوم العلاقات العامة في شركة سونلغاز على الوسائل المكتوبة والشفوية والالكترونية في اتصال وانسجام المعلومات. مساهمة العلاقات العامة في تحسين الاداء الوظيفي للشركة.ملخص الدراسة ومن اجل الاجابة على اشكالية بحثنا فقد اعتمدنا على المنهج الوصفي وهذا لكونه الاكثر ملائمة لموضوع الدراسة واعتمدنا على القابلة والملاحظة كأدوات لجمع البيات وقد قمنا باختيار مجتمع بحثنا والمتمثلة في سبعة موظفين من مديرية توزيع الكهرباء والغاز لولاية تيندوف وقد اوصينا في دراسنا هذه لمجموعة من التوصيات والمقترحات اهمها: الاعتراف بأهمية ودور العلاقات العامة وضرورة الالتزام بنظام علمي في استخدام التحفيز ومشاركة الموظفين في اتخاد القرارات حتى يتمكن المكلف بالعلاقات العامة من اداء عمله وتطبيق برنامجه. تخصيص مكتب خاص بمراقبة نشاطات العلاقات العامة كما ينبغي بتوفير مساعدين للمكلف بالعلاقات ليبقى جهاز قائم بذاته. توفير للعمال الجو والبيئة المناسبة للعمل من اجل اداء حسن. توفير الوسائل العامة من اجل تسهيل وتحسين اداء الموظفين. بناء هيكل خاص بالشركة او مقر خاص بالشركة .ملخص الدراسة Study Summary: The problem of the study in the role of public relations in improving the performance of employees at the Sonlgaz in TINDOUF foundation And the reasons that led us to choose this subject and our attempt to enrich the subject of public relations and its progress in the economic aspect and specifically in the Sonlgaz Foundation for being primarily a service of an economic nature and neglect the role of public relations in most institutions. In our study, we adopted a number of questions: ● what are the relationship activities and what is their position in the company? ● what is the contribution of PR in improving job performance? ● What are the difficulties facing the employee within the company? We also relied on a set of hypotheses • The Public Relations Department is based on activities to improve the functionality of Sunlagaz Tindouf. ● Sonalgaz's public relations are based on written, oral and electronic means of communicating and harmonizing information ● The contribution of public relations in improving the performance of the company.ملخص الدراسة In order to answer the problem of our research, we have relied on the descriptive approach and this is because it is the most appropriate for the subject of study and we relied on the midwife and observation as tools for gathering the bytes and we have chosen our research community of seven employees of the Directorate of Electricity and Gas Distribution of Tindouf State and we have recommended In this study we have a set of recommendations and proposals, the most important ones  Recognize the importance and role of public relations and the need to adhere to a scientific system in the use of motivation and participation of employees in decision-making so that the public relations officer can perform his work and the implementation of his program.  Assign a special office to monitor public relations activities and provide liaison assistants to remain a stand-alone body.  Provide workers with the right atmosphere and environment to work for good performance.  Provide public means to facilitate and improve the performance of employees.  Build a company structure or company headquarters.ا
انموذجا SDC مديرية توزيع الكهرباء والغاز
Keywords: العلاقات العامة؛الاداء الوظيفي؛المؤسسات الاقتصادية؛